Base-Promoted Internal Redox-Cyclisation Reactions - Shaaban, Saad; Peng, Bo; Maulide, Nuno (Synlett, 2013)
A new internal, base-mediated redox-cyclisation reaction has been discovered and developed. In this transformation, the sacrificial reduction of an alkynyl moiety to an alkene allows direct functionalisation of an α-amino C–H bond. This approach allows the preparation of several 1,3-oxazinane derivatives in an atom-efficient manner.
Keywords: C–H activation; C–H functionalisation; redox; cyclisation; pyrrolidine